CSC566: Image Processing / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics And Media (Universiti Teknologi MARA (UiTM), 2018)
This course is intended to acquaint students with the fundamental understanding of image processing, its most common image processing techniques and its mathematical foundations. It is structured to enable students to understand the underlying principles of digital image formation and related technical aspects, image enhancement, segmentation, and their applications in various industrial areas. Upon completion of the course, the student should be competent in applying the concepts in an image processing project, and should be capable of pursuing research in image processing areas.